Robotic Resection of 3 Cm and Larger Thymomas is Associated with Low Perioperative Morbidity and Mortality. Issue 5 (September 2016) - Wilshire, Candice L.; Vallières, Eric; Shultz, Dale; Aye, Ralph W.; Farivar, Alexander S.; Louie, Brian E.
Objective: The approach to thymoma resection has usually been determined by tumor size, although established guidelines do not exist. Minimally invasive approaches have been limited to tumors smaller than 5 cm, although 3 cm has been the suggested cutoff for performing an adequate oncologic procedure. No study has compared the perioperative outcomes of patients with 3 cm or larger tumors resected robotically versus sternotomy. Methods: We reviewed patients who underwent resection of 3 cm or larger thymomas from 2004 to 2014. Patients were divided based on approach: robotic and open thymectomy/thymomectomy. Results: Forty patients with tumors ranging from 3 to 13 cm were evaluated, 23 robotic and 17 open. Patient and tumor characteristics were similar. An R0 resection was primarily achieved: robotic, 91% (21/23); and open, 88% (15/17); P = 0.832. Adjuvant radiation rates were statistically equivalent: robotic, 17% (4/23) versus open, 41% (7/17); P = 0.191. Major postoperative complications were comparable: robotic, 4% (1/23) versus open, 29% (4/17); P = 0.184. Median chest tube duration was shorter for robotic (1 day) versus open (3 days); P = 0.001. The robotic approach had a shorter median intensive care unit stay compared to open (0 days vs 1day); P = 0.024. The median hospital stay was shorter for robotic (2 days) versus open (5 days); P < 0.001. Conclusions: In 3 cm or larger thymomas, robotic thymectomy is feasible based on the ability to achieve a complete resection with similar adjuvant radiation therapy rates. Perioperatively, robotic thymectomy is associated with lower morbidity; and shorter chest tube duration, intensive care unit stay, and hospital stay compared to open. However, on-cologic outcomes are immature and require prolonged surveillance.